Cuando la ley fundamental desbarata: Los conservadores y la constitución de 1857 - Pani, Erika (Jahrbuch für Geschichte Lateinamerikas, 2018)
In the aftermath of the instability that characterized Mexican national politics in the decades after independence and after ten years of war, the 1857 constitution became a stable juridical framework. This article analyzes the arguments of its Conservative critics, who condemned it as anarchic and incompatible with the character of a Catholic people. It also examines the legal proposals for centralization and administrative consolidation they made for the military and monarchical regimes that governed from Mexico City between 1858-1860 and 1863-1867.